2017
DOI: 10.3389/fncel.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Translational Magnetic Resonance Imaging in Animal Models of Stress and Depression

Abstract: Magnetic resonance imaging (MRI) is a valuable translational tool that can be used to investigate alterations in brain structure and function in both patients and animal models of disease. Regional changes in brain structure, functional connectivity, and metabolite concentrations have been reported in depressed patients, giving insight into the networks and brain regions involved, however preclinical models are less well characterized. The development of more effective treatments depends upon animal models tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 122 publications
(168 reference statements)
0
7
0
Order By: Relevance
“…However, the DTI and DKI results are less clear-cut. Microstructural disruption in WM, axonal degeneration, and demyelination in depression are generally believed to produce higher RD and MD and lower FA in both patients with depression ( 11 , 59 , 60 , 61 ) and animal models of depression ( 62 , 63 ), such as the Wistar–Kyoto strain genetic model ( 14 ) and chronic unpredicted mild stress model ( 13 ). Keeping in mind that relating DTI and DKI measures to tissue microstructure is difficult, our observation of higher FA values being driven by a decrease in RD and MD contradicts the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the DTI and DKI results are less clear-cut. Microstructural disruption in WM, axonal degeneration, and demyelination in depression are generally believed to produce higher RD and MD and lower FA in both patients with depression ( 11 , 59 , 60 , 61 ) and animal models of depression ( 62 , 63 ), such as the Wistar–Kyoto strain genetic model ( 14 ) and chronic unpredicted mild stress model ( 13 ). Keeping in mind that relating DTI and DKI measures to tissue microstructure is difficult, our observation of higher FA values being driven by a decrease in RD and MD contradicts the above-mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced total brain and hippocampal volume has been observed in several animal models, such as a SCZ model 46 , a MDD model 47 , ASD model 48 , and a post-traumatic stress disorder (PTSD) model 49 . Smaller globus pallidus in Negr1 −/− mice is indicative of disrupted cortico-basal ganglia circuitry and/or connections of the limbic pallidum with the dopaminergic system 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Laine et al demonstrated that mice exposed to chronic social defeat stress showed significantly more activation in several brain regions known to regulate depressive and anxiety‐like behavior 21 . In a recent review, McIntosh et al concluded that increased lateral ventricular volume and decreased hippocampal volume are relatively consistent hallmarks in both patients with MDD and animals model 22 …”
mentioning
confidence: 98%